Fenbendazole improves pathological and functional recovery following traumatic spinal cord injury - Yu, Chen Guang (2013)
During a study of spinal cord injury (SCI), mice in our colony were treated with the anthelmintic fenbendazole to treat pinworms detected in other mice not involved in the study. As this was not part of the original experimental design, we subsequently compared pathological and functional outcomes of SCI in female C57BL/6 mice who received fenbendazole (150 ppm, 8 mg/kg body weight/day) for four weeks prior to moderate contusive SCI (50 kdyn force) as compared to mice on the same diet without added fenbendazole. The fenbendazole-treated mice exhibited improved locomotor function, determined using the Basso mouse scale, as well as improved tissue sparing following contusive SCI. Fenbendazole may exert protective effects through multiple possible mechanisms, one of which is inhibition of the proliferation of B lymphocytes, thereby reducing antibody responses. Autoantibodies produced following SCI contribute to the axon damage and locomotor deficits. Fenbendazole pretreatment reduced the injury-induced CD45R-positive B cell signal intensity and IgG immunoreactivity at the lesion epicenter six weeks after contusive SCI in mice, consistent with a possible effect on the immune response to the injury. Fenbendazole and related benzimadole antihelmintics are FDA approved, exhibit minimal toxicity, and represent a novel group of potential therapeutics targeting secondary mechanisms following SCI.